An improved 1-Ï† rectifier system using fuzzy logic control with 3-Ï† variable frequency drive - Kiran Kumar, M; Almaj, SK; S. Srikanth, K (International Journal of Engineering and Technology, 2018)
A 3-Î¦ VFD steam fed from a 1-Î¦ AC supply. To stop more stresses in the components within the drive and within the input supply,Â the drive output power should be restricted. To beat this problem, several VFD makers decided that drive to be de-rated. As often as possible, the driveâ€™s output frequency is limited, supported the dc voltage ripple hence the DC capacitors arenâ€™t overstressed. Through the tradional technique decrement of strain within the DC Capacitors, it doesnâ€™t consider the stresses in other parts of the drive, particularly the diodes at the input and terminal blocks of input. During this paper, brand new fuzzy controller based technique for the protection of the drive the motor Â Â current with FLC is projected. The motor Â current is shown to possess info relating the stresses in numerous elements of the VFD together with the diodes at the input, terminal blocks of the input, and therefore the Dc capacitors. The o/p power is projected to be restricted by decreasing the o/p frequency supported the avg and ripple abundancy of the quadrature axis current rather than the dc voltage ripple. To prove this conception, a comparison is made between fuzzy logic controller based technique employing a less power VFD fed from a 1-Î¦ ac, and the conventional dc voltage ripple based frequency technique.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â